Optimization of Operational Management System on Ships for Cost and Time Efficiency - Sadewi, Septria; Siladjaja, Muljanto (Dinasti International Journal of Digital Business Management, 2025)
The shipping industry plays a critical role in global trade, with over 80% of international trade being transported by sea. However, rising operational costs and inefficiencies in shipping operations, such as fuel consumption, route management, and port turnaround times, pose significant challenges. This study aims to explore optimization strategies for ship operational management to enhance cost efficiency and reduce travel time. Using a qualitative approach, data was collected from academic journals, books, and online sources, focusing on best practices and technological innovations in the maritime sector. The findings highlight the importance of data-driven management systems, such as navigation algorithms and Internet of Things (IoT) technologies, in reducing fuel consumption and improving route optimization. Furthermore, improving port infrastructure and managing waiting times at ports are identified as key factors in enhancing overall operational efficiency. This research provides recommendations for implementing an integrated operational management system that combines technology, data utilization, and effective time management. The results suggest that optimizing ship management systems can significantly reduce operational costs and improve competitiveness in the global shipping market, contributing to the development of maritime policies and strategies for enhancing logistics efficiency.